A checklist of Polyplacophora (Mollusca) from the Fiji islands - Schwabe, Enrico; Sirenko, Boris I.; Seeto, Johnson (Zootaxa, 2008)
A compiled list of Fiji Islands chitons, including an updated chresonymy list and identification key, is provided. To the nine species previously known from the literature ten more are added. Of the 19 species now known from Fijian waters, one is a deep-water species and two are also known from fossils. A redescription of Callochiton neocaledonicus Kaas & Van Belle, 1990, and a detailed description of subadult specimens of Choneplax littlerorum Sirenko, 2003 are herein provided. Chiton spinosetatus Bergenhayn, 1930 is here regarded as a synonym of Chiton subassimilis Souverbie in Souverbie & Montrouzier, 1866. A lectotype designation is herein made for one of the numerous syntypes of Cryptoplax jugosus Bergenhayn, 1930 and for one of the two syntypes of Chiton reticulatus Nierstrasz, 1905 to stabilize the type localities for these species. For the same reason, and to clarify the confusing type status of Lepidopleurus niasicus Thiele, 1906, a lectotype is also selected from the three available syntypes. Acanthopleura nigropunctata Carpenter, 1865 and Tonicia novemrugata Bergenhayn, 1930, formerly placed in Tonicia, are both reassigned to the genus Lucilina on the basis of radular differences of both genera (second lateral tooth quadricuspid in Lucilina vs. unicuspid in Tonicia) and the geographic isolation of the Tonicia, of which species occur in central and south American waters only.